Decentralization of minimum wage setting in Russia: Causes and consequences - Anna Lukiyanova; Nina Vishnevskaya (Universität Duisburg-Essen, Institut für Betriebswirtschaft und Volkswirtschaft (IBES), 2014)
[Final remarks] Our findings suggest that the decentralization reform of the MW setting mechanism accelerated the growth of the wage floor for Russian workers and narrowed the variation in the minima between regions. At the same time, the coexistence of the federal and regional minimum wages has led to new imbalances. All these mean that the reform of the minimum wage setting mechanism in Russia cannot be considered final and further steps are required for better functioning of this institute.
Keywords: 330